2023
DOI: 10.1177/03635465231164952
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Meniscal and Articular Cartilage Injury in the PLUTO Cohort

Abstract: Background: Anterior cruciate ligament (ACL) injuries in adults are frequently accompanied by meniscal and articular cartilage damage. However, little is known regarding the association, if any, between physical maturity, hypermobility, or bone bruising and these associated injuries in skeletally immature patients with ACL tears. Purpose: To determine if physical maturity, hypermobility, and/or bone bruising is associated with concomitant meniscal and articular cartilage injury in skeletally immature patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…However, the evidence supporting the efficacy of reconstruction in preventing cartilage injury remains insufficient. A study has shown that approximately 11.4% of ACL tear patients are diagnosed with cartilage injury [ 8 ], accompanied by pain and functional impairments. The resulting pain and loss of function significantly affect individuals' physical well-being, contributing to substantial economic burdens in developed countries, representing 1%–2.5% of the gross domestic product [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence supporting the efficacy of reconstruction in preventing cartilage injury remains insufficient. A study has shown that approximately 11.4% of ACL tear patients are diagnosed with cartilage injury [ 8 ], accompanied by pain and functional impairments. The resulting pain and loss of function significantly affect individuals' physical well-being, contributing to substantial economic burdens in developed countries, representing 1%–2.5% of the gross domestic product [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Articular cartilage injury (ACI) refers to the damage or destruction of the cartilage on the surface of joints. There are various factors that can lead to ACI, including accidental falls, sports injuries or accidents resulting in joint twists or impacts; prolonged or excessive use of a joint; inflammatory joint diseases, such as rheumatoid arthritis; and other inflammatory conditions [ 1 ]. Repairing articular cartilage damage is challenging due to its limited self-repair ability caused by the absence of blood vessels and nerves [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cartilage injuries, especially those involving articular cartilage, are prevalent among physically active individuals. Such injuries predominantly affect the knee but can manifest in other aforementioned joints ( Matava et al, 2023 ). The underlying causes of cartilage damage are manifold, ranging from forceful impacts due to sports injuries or accidental falls to progressive wear and tear over extended periods of usage.…”
Section: Introductionmentioning
confidence: 99%